Andrea Fraser - official welcome Kunstverein in Hamburg, September 3, 2003 - Fraser, Andrea 1965- (Andrea Fraser, 2003)
Official Welcome questions the relationship between artists and patrons: at one point, Fraser completely disrobes to suggest the inherent exhibitionism involved in presenting art. The intelligence, clarity, and forcefulness of such performances have ensured the Fraser's oeuvre remains a touchstone for critically engaged art of the 1990s and beyond
Title from disc label
Official Welcome was commissioned by and first performed at the MICA Foundation, New York, November 28, 2001
Keywords: Fraser, Andrea -- 1965-; Geschichte 2003; Aufführung; Fraser, Andrea; Nonfiction films; Film; DVD-Video